Self-governance experience as an element of management in education - Horodyska, Olga (Marijampolės kolegija, Lietuva, 2021)
Research is aimed at substantiation of the one’s self-governance experience as successful management obligatory condition in the education management process. Education is one on the top of the managerial practice list inasmuch as it aimed at cultivation of definite skills and competences among students for their further professional activity. Management as administrative, governance process has subject and object as the basic elements; they presuppose each other and represent the united system of management process. But in contemporary world it’s ineffectively to consider management only as a process of out influence directed at definite objects. To realize management strategy successfully each human one in the process must function consciously and responsively, and it is impossible without free conscious choice, full-value experience, responsible self-governance and conduct. Even as a management object the self is not only the area for management subject’s skills application. The one (self) is not passive but necessarily active constituent of management process. It’s significantly important to investigate management as the usage of individual field of one’s experience for general governance purposes, and it is particularly important in educative activity. That’s why research in management must be initiated with investigation of one’s experience as an open field of possibilities including conduct, governing (self-governance and governmentality) and care of the self as the essential aspects of freedom and personal self-realization. Only taking into account all these requirements investigation of management in education area seems to be relevant and forward-looking indeed.

Švietimas yra vienas iš svarbiausių valdymo praktikoje, nes juo siekiama ugdyti aiškius įgūdžius ir kompetencijas tarp studentų jų tolesnei profesinei veiklai. Valdymas kaip administracinis, valdymo procesas turi subjektą ir objektą kaip pagrindinius elementus; jie suponuoja vienas kitą ir atstovauja vieningai valdymo proceso sistemai. Tačiau šiuolaikiniame pasaulyje neefektyviai vertinti valdymą tik kaip įtakos procesą, nukreiptą į tam tikrus objektus. Norint sėkmingai įgyvendinti valdymo strategiją, kiekvienas žmogus šiame procese turi veikti sąmoningai ir jautriai, ir tai neįmanoma be laisvo sąmoningo pasirinkimo, pilnos vertės patirties, atsakingos savivaldos ir elgesio, kaip valdymo objektas savarankiškai yra ne tik valdymo subjekto įgūdžių taikymo sritis. Vienas (aš) nėra pasyvus, bet būtinai aktyvus valdymo proceso dalyvis. Labai svarbu ištirti valdymą kaip individualios savo patirties srities naudojimą bendriems valdymo tikslams, ir tai ypač svarbu švietėjiškos veiklos srityje. Štai kodėl valdymo tyrimai turi būti pradėti tiriant savo patirtį kaip atvirą galimybių lauką, įskaitant elgesį, valdymą (savivaldą ir valdymą) ir rūpinimąsi savimi kaip esminius laisvės ir asmeninės savirealizacijos aspektus. Tik atsižvelgiant į visus šiuos reikalavimus išryškėja, kad švietimo srities valdymo tyrimas yra svarbus ir orientuotas į ateitį.
Savivaldos patirtis kaip švietimo valdymo elementas
Keywords: education; management; human; self-governance; governmentality; experience; care of the self; švietimas; vadyba; žmogus; savivalda; valdžia; patirtis; rūpinimasis savimi